The Pepper MAP Kinase CaAIMK1 Positively Regulates ABA and Drought Stress Responses - Jeong, Soongon; Lim, Chae Woo; Lee, Sung Chul (Frontiers in Plant Science, 2020)
Protein phosphorylation and dephosphorylation are important mechanisms that regulate many cellular processes. Protein kinases usually function in the regulation of the stress response by adjusting activity via phosphorylation of target proteins. Here, we isolated CaAIMK1 (Capsicum annuum ABA Induced MAP Kinase 1) from the pepper leaves that had been subjected to drought stress. CaAIMK1 transcripts were induced by drought, abscisic acid (ABA), high salinity, and H2O2; further, the CaAIMK1 protein localised in the nucleus and cytoplasm. We performed genetic studies using CaAIMK1-silenced pepper plants and CaAIMK1-overexpressing (OX) Arabidopsis plants. CaAIMK1-silenced pepper plants showed a drought-sensitive phenotype characterised by altered ABA signalling, including low leaf temperatures, and large stomatal apertures. CaAIMK1-OX plants exhibited a contrasting drought-tolerant phenotype characterised by decreased levels of transpirational water loss and increased expression levels of Arabidopsis stress-related genes. In CaAIMK1K32N-OX transgenic Arabidopsis plants, sensitivity to ABA and drought was restored. Collectively, these results demonstrate that CaAIMK1 positively regulates the drought stress response via an ABA-dependent pathway.